Contesting the EU in times of crisis: The Front National and politics of Euroscepticism in France. (August 2018) - Ivaldi, Gilles
This article examines the performance and party system diffusion of Euroscepticism of the French Front National (FN) during recent European crises. The article argues that Europe's successive crises since 2008 have been essentially 'absorbed' by the FN into its existing Eurosceptic framework which is guided by its radical right-wing ideology. While allowing the FN to successfully mobilize issues and grievances about the European Union (EU), Euroscepticism is, however, significantly impeding its strategy of governmental credibility. The article identifies the main political outcomes of these crises and finds differences in impact between the different EU crises on party competition over Europe. These findings provide insight into the relationship between the radical Right, Euroscepticism, and party competition. They also inform our current knowledge of Euroscepticism in French politics, and changes that EU crises have triggered, according to party system location and whether FN influence can be postulated.